EHLSSA: Europe-Wide Online Learning For Seniors - Lipphardt, Anne-Marie; Slyschak, Anna (Revista Ariadna; cultura, educación y tecnología, 2016)
Technology dominates the future and it is increasingly penetrating culture and society. In the course of this trend, online learning is gaining importance and becoming a crucial and integral component of lifelong learning. Still, the group of senior citizens is one of the groups that are predominantly excluded from using new technologies, though digital devices provide each citizen with new opportunities and perspectives. The EHLSSA project– European Home Learning Service for Seniors Association – takes this finding as its starting point and develops e-learning solutions for seniors around Europe. The importance and added-value of specially adapted e-learning models for this highly heterogeneous group is presented in this articl
Keywords: senior learners; e-learning; pedagogy and didactics.